2005
DOI: 10.1093/toxsci/kfi150
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to the Fungicide Prochloraz Feminizes the Male Rat Offspring

Abstract: Prochloraz is a commonly used fungicide that has shown multiple mechanisms of action in vitro. It antagonizes the androgen and the estrogen receptors, agonizes the Ah receptor, and inhibits aromatase activity. In vivo prochloraz acts antiandrogenically in the Hershberger assay by reducing weights of reproductive organs, affecting androgen-regulated gene expressions, and increasing luteinizing hormone (LH) levels. The purpose of this study was to investigate reproductive toxic effects after exposure during gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 34 publications
8
96
1
3
Order By: Relevance
“…There is insufficient evidence to assess the risk of tested pesticides to human health because of a lack of data. However, to our knowledge, all of the pesticides (with the possible exception of fenitrothion; Okahashi et al 2005;Turner et al 2002) identified as in vitro AR antagonists in our study have also been reported to have anti androgenic effects in vivo in animal models (Anway et al 2006;Gray et al 1999;Lambright et al 2000;McIntyre et al 2002;Ostby et al 1999;Sinha et al 2001;Taxvig et al 2007;Uzumcu et al 2004;Vinggaard et al 2005). We also identified 7 compounds that appeared to be androgenic because they stimulated activity in the absence of DHT.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…There is insufficient evidence to assess the risk of tested pesticides to human health because of a lack of data. However, to our knowledge, all of the pesticides (with the possible exception of fenitrothion; Okahashi et al 2005;Turner et al 2002) identified as in vitro AR antagonists in our study have also been reported to have anti androgenic effects in vivo in animal models (Anway et al 2006;Gray et al 1999;Lambright et al 2000;McIntyre et al 2002;Ostby et al 1999;Sinha et al 2001;Taxvig et al 2007;Uzumcu et al 2004;Vinggaard et al 2005). We also identified 7 compounds that appeared to be androgenic because they stimulated activity in the absence of DHT.…”
Section: Discussionmentioning
confidence: 53%
“…These compounds are newly formulated fungicides (dimethomorph, 2007; fludioxonil, 2008; fenhexamid, 2001), which are stable on food commodities (> 70% of the parent compound) and remain unchanged on the commodity when reaching the consumer (EFSA 2007(EFSA , 2010a(EFSA , 2010b. Dimethomorph and fenhexamid belong to the fungicide group of sterol bio synthesis inhibitors (Leroux 2004), as do the in vivo anti androgenic conazoles (e.g., Taxvig et al 2007) and imidazoles (Vinggaard et al 2005). A study of the sterol biosynthesis inhibitors imazalil, propi conazole, triadimefon, triadimenol, and prochloraz indicated that all inhibited aromatase in human placental microsomes (Vinggaard et al 2000), but to our knowledge, effects of dimethomorph and fenhexamid on steroido genesis in mammalian cells have not been assessed.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Prochloraz is a widely used pesticide that has been demonstrated to have endocrine activity. In animals, it has been shown to cause adverse reproductive outcomes in the male offspring after exposure during foetal life [35][36][37][38]. Prochloraz is known to demasculinize male rat foetuses and virilize female foetuses; however, as clinical studies of environmental chemicals are not carried out, little is known about human effects of this compound.…”
Section: A Case Study: Computational Systems Biology Applied On Prochmentioning
confidence: 99%